Dampak Putusan Mahkamah Konstitusi dalam Judicial Review terhadap Sistem Hukum di Indonesia - Rafli Akbar Rabbani; Riva Nurkania; Soraya Salimah; Utang Rosidin (ALADALAH: Jurnal Politik, Sosial, Hukum dan Humaniora, 2026)
The Constitutional Court (CC) was established following the amendments to the 1945 Constitution of the Republic of Indonesia and holds a strategic role in upholding constitutional supremacy through its authority of judicial review. Although CC decisions are final and binding, their implementation often encounters political resistance, legislative delays, and weak institutional commitment, which may undermine legal certainty and constitutional governance. This study employs a normative juridical method using a statutory approach and library research, focusing on selected Constitutional Court decisions and their follow-up mechanisms. The findings show that the effectiveness of CC rulings is not solely determined by their juridical force, but largely depends on the responsiveness and synergy of legislative and executive institutions. Inconsistent implementation of CC decisions has led to regulatory gaps and uncertainty within the legal system. Therefore, strengthening institutional commitment and harmonizing judicial and legislative functions are essential to reinforce legal certainty, justice, and constitutional democracy in Indonesia.